Rare case of chronic suppurative otitis media with gradenigo syndrome - ., Shiffali; ., Priyanka; Sandhu, Kulwinder Singh; Singh, Jagdeepak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
We report a case of sixth nerve palsy as a rare complication of acute otitis media (apical petrositis). The clinical triad of symptoms consisting of retro-orbital unilateral pain related to trigeminal nerve involvement, diplopia due to sixth nerve palsy and persistent otorrhea is known as Gradenigo syndrome. The patient was treated with intravenous antibiotics along with modified radical mastoidectomy and had complete resolution of his symptoms.